Large cell neuroendocrine carcinoma of the submandibular gland: a case report and literature review - Mascitti, M.; Luconi, E.; Togni, L.; Rubini, C. (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2019)
Neuroendocrine tumors (NET) are a heterogeneous group of malignancies with a broad spectrum of histomorphologies, tissue origins, and clinical outcomes, which arise from neural crest cells with neuroendocrine differentiation. Salivary gland tumors account for 3-6% of all head and neck neoplasms, while large cell neuroendocrine carcinomas (LCNEC) of the salivary gland are extremely rare, with few cases reported in literature, and only 5 cases involving submandibular gland. The rarity of these tumors in salivary glands is probably related to the scarcity of neuroendocrine cells in this tissue, whose presence is still a matter of debate. Regardless of their low frequency, it is imperative to differentiate these tumors from the much more common squamous cell carcinomas and metastatic NETs, due to different therapeutic approach and prognosis. In this paper, we report the case of a 21-year-old man, with a LCNEC involving a submandibular gland followed by several recurrences over the years. In addition, we include a comprehensive review of the available literature on this topic.